Development of hydrophobic metakaolin hollow fibre membrane for membrane distillation application - Hubadillah, Siti Khadijah (Penerbit UTM Press, 2019)
Metakaolin hollow fibre membranes (MHFM) was prepared by a combined phase inversion and sintering method for direct contact membrane distillation (DCMD) application. Four hydrophobic metakaolin hollow fibre membranes (h-MHFM) sintered at different temperatures (1200ºC to 1500ºC) were successfully prepared by grafting 1H,1H,2H,2H-perfluorodecyltriethoxysilane on the MHFM. Prior to the grafting process, the MHFM was hydrolysed with a mixture of ethanol and water with the ratio of 1:2 for 24 hours. The effectiveness of the hydrophobization on each MHFM was assessed using contact angle measurement, scanning electron microscopy (SEM) and three-point bending test. It was found that the increasing sintering temperature improved the mechanical strength from 117.6 MPa to 182.3 MPa. Further increment in mechanical strength was also observed after the modification with fluoroalkylsilane (FAS). The contact angle of the membrane was enhanced up to 120˚ after modification. In general, the membrane prepared at low sintering temperature of 1200°C exhibited the highest DCMD performance with the water vapor flux of 17.5 kg/m2h due to the sufficient pore size for the vapor to pass through the membrane structure.